Learning Motivation in the Perspective of Hadith: A Study of Several Hadiths in the Kitab Shahih Bukhari - Raja Muhammad Kadri; Putri Intan Purwari; Rahmat; Irfal Khairul Fadri; Arwansyah Kirin (Al Bahri: Journal of Islamic Education, 2025)
Motivation is one of the most important variables in improving the quality of learning. This is in accordance with the hadiths conveyed by the Prophet Muhammad SAW. Therefore, the author will explore how learning motivation is addressed in the perspective of hadith, particularly those found in the Sahih Bukhari. The research method used in this article is a qualitative approach with content analysis. From the analysis, the author identified at least four hadith related to learning motivation. The motivation for learning from the perspective of these hadiths is as follows: 1) Motivation for learning stems from the determination of the learner, 2) The Prophet Muhammad SAW as an educator often motivated others, 3) Hadiths related to motivation align with the theory of learning motivation proposed by education experts. The author hopes that the hadiths collected in this research will be utilised by Islamic Education teachers, whether in school or madrasah.